INOVASI MOTIF KASAB ACEH DI KABUPATEN PIDIE SEBAGAI UPAYA PENGEMBANGAN EKONOMI KREATIF MELALUI PENDEKATAN SOCIOPRENEURSHIP - Nurazizah Azizah; fiesca maini asri; Rita Mulyani (Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2026)
Kasab Aceh is a cultural heritage that has high artistic, historical, and local identity value. However, the increasingly competitive development of the creative industry demands innovation to maintain the sustainability and increase the economic value of kasab products. This study aims to analyze the innovation of the Kasab Aceh motif in Pidie Regency as an effort to develop the creative economy through a sociopreneurship approach. The research method used is a qualitative method with a descriptive approach through observation, interviews, and documentation of kasab business actors, craftsmen, and the local community. The results show that the innovation of the Kasab Aceh motif is carried out by adapting elements of local culture, flora, fauna, and regional symbols without eliminating the traditional values ​​​​contained within it. The sociopreneurship approach is implemented through community empowerment, improving craftsman skills, creating jobs, and strengthening community-based marketing networks. This innovation not only increases the competitiveness of kasab products in the market but also has a social impact in the form of increased community income and preservation of local culture. Therefore, the innovation of the Kasab Aceh motif based on sociopreneurship can be an effective strategy in supporting the development of a sustainable creative economy in Pidie Regency..